Outcome of colorectal cancer patients treated with combination bevacizumab therapy: a pooled retrospective analysis of three European cohorts from the angiopredict initiative - Betge, Johannes; Belle, Sebastian; Zhan, Tianzuo; Härtel, Nicolai; Kripp, Melanie; Hofheinz, Ralf-Dieter; Gaiser, Timo; Ebert, Matthias; Schulte, Nadine (Digestion, 2016)
Background/Aims: This study is aimed at analyzing the survival rates and prognostic factors of stage IV colorectal cancer patients from 3 European cohorts undergoing combination chemotherapy with bevacizumab. Methods: Progression free-survival (PFS) and overall survival (OS) were analyzed in 172 patients using the Kaplan-Meier method and uni- and multivariable Cox proportional hazards regression models. Results: The median PFS was 9.7 and the median OS 27.4 months. Patients treated at centers in Germany (n = 97), Ireland (n = 32), and The Netherlands (n = 43) showed a median PFS of 9.9, 9.2, and 9.7 months, OS of 34.0, 20.5, and 25.1 months, respectively. Patients >65 years had a significantly shorter PFS (9.5 vs. 9.8 months) but not OS (27.4 vs. 27.5 months) than younger patients. High tumor grade (G3/4) was associated with a shorter PFS, T4 classification with both shorter PFS and OS. Fluoropyrimidine (FP) chemotherapy backbones (doublets and single) had comparable outcomes, while patients not receiving FP backbones had a shorter PFS. In multivariable analysis, age and non-FP backbone were associated with inferior PFS, T4 classification and therapy line >2nd were significantly associated with poor PFS and OS. Conclusion: The observed survival rates confirm previous studies and demonstrate reproducible benefits of combination bevacizumab regimens. Classification T4, non-FP chemotherapy backbone, and age >65 were associated with inferior outcome.